A Monolayer Frequency-Selective Surface for Wideband Shielding Application with Adequate Out-of-Band Separation and Angular Stability - Ayan Chatterjee; Pratik Dey; Kousik Roy; Susanta Kumar Parui (International Journal of Antennas and Propagation)
In the proposed paper, a monolayer band-stop frequency-selective surface (FSS) is structured and analyzed for application in wideband shielding. The paper proposes an organized step-by-step method to design the frequency-selective surface (FSS) to achieve enhanced shielding effectiveness (SE) over the entire band. The suggested FSS comprises of tripole-shaped unit cells on both sides of a monolayer FR-4 substrate to offer adequate shielding over the band of 3.2–8.82 GHz which includes both C- and X-bands. The operating band of the FSS achieves ultrawideband shielding by means of 93% bandwidth with 60–100 dB shielding effectiveness. Experimental data are employed for the characteristics that are fairly well congruent to simulated results. Higher angular stability beyond 80° characterizes the proposed FSS. A wide range of potential uses for the proposed design exists, including microwave shielding, wideband filtering, as well as radar cross-section (RCS) reduction, among others. The out-of-band RCS reduction capability of the FSS is also investigated and presented in this paper.